Impact of stakeholder theory on quantity and quality reporting of corporate social responsibility disclosure / Noreena Md Yusoff, Roshayani Arshad and Ahmad Akbal Mohamed - Md Yusoff, Noreena; Arshad, Roshayani; Mohamed, Ahmad Akbal (2013)
Stakeholder theory has been used extensively in order to understand factors affecting disclosure level made by companies. However, not many studies have been done regarding such topic involving companies in a developing country such as Malaysia. Thus, this study was carried out using stakeholder theory to analyze the determinants for Corporate Social Responsibility (CSR) disclosure. In this study, to measure the CSR disclosure, the authors had used words count method and rating method to measure quantity and quality reporting respectively. Thus, Malaysian public listed companies’ data from 2010 were examined to find out the quantity and quality of disclosure made. Three determinants of stakeholder theory namely, government power (GP), creditor power (CP) and shareholder power (SP), are used to explain the influence for CSR disclosure. The findings suggest government power, as a proxy of environmental sensitive industry, and creditors’ power are significant positive and significant negative respective factors that influence the quantity and quality of CSR disclosure made by companies. The empirical results provide evidence that the application of stakeholder theory can contribute towards how the corporate entities should behave and this particularly can determine how information should be disclosed to users’ financial statement